2010
DOI: 10.1380/ejssnt.2010.261
|View full text |Cite
|
Sign up to set email alerts
|

Study of H:Si(113)2&times;2 Structure by Scanning Tunneling Microscopy and <i>Ab Initio</i> Calculation

Abstract: The H:Si(113) structure has been studied by scanning tunneling microscopy and ab initio caluculation. After exposing hydrogen atoms on a clean Si(113) surface, 2×n:H (n = 2,3) structures form. High-resolution STM images reveal that these structures show three types of protrusions. Islands growing one-dimensionally are observed on the local surface area. We performed an ab initio calculation for several possible structural models of the 2×2:H structure. Comparison of observed STM images and simulated images obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
3
2
Order By: Relevance
“…Hydrogen, bucking the trend in this case, has a transition μ higher than iodine, reflecting the relative weakness of the Si–H bond compared to silicon–halogen bonds. In all cases, we find that the difference between the structures proposed by Flege et al and Hara et al . is insignificant and that we cannot reasonably distinguish between the two, within the accuracy of this method.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…Hydrogen, bucking the trend in this case, has a transition μ higher than iodine, reflecting the relative weakness of the Si–H bond compared to silicon–halogen bonds. In all cases, we find that the difference between the structures proposed by Flege et al and Hara et al . is insignificant and that we cannot reasonably distinguish between the two, within the accuracy of this method.…”
Section: Resultscontrasting
confidence: 57%
“…In all cases, we find that the difference between the structures proposed by Flege et al 26 and Hara et al 25 is insignificant and that we cannot reasonably distinguish between the two, within the accuracy of this method. 26 structure for H, F, Cl and Br and the Hara et al 25 structure for I.…”
Section: ■ Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Experimentally, the bare Si(113) surface is found to reconstruct with a 3 × 2 symmetry, 33 which may be explained by the adatom-dimerinterstitial (ADI) model of Dabrowski et al, 34 in which a 6-foldcoordinated subsurface interstitial atom is present. Combined experimental/computational studies have found two possible saturation terminations for Group VII atoms on the Si(113) surface: one by Flege et al for chlorine and a second by Hara et al 35 for hydrogen. Although both terminations appear in practice to consist of (2 × n) motifs for several values of n, these appear to be variations on a basic 2 × 2 structure.…”
Section: ■ Surface Energiesmentioning
confidence: 99%